A teacher's guide to multisensory learning [ improving literacy by engaging the senses - Baines, Lawrence (Gale virtual reference library, 2008)
"In A Teacher's Guide to Multisensory Learning: Improving Literacy by Engaging the Senses, Lawrence Baines shows teachers how to engage students through hands-on, visual auditory, and olfactory stimuli and link the activities to relevant academic objectives." -- Jacket